THE EFFECT OF USING DIFFERENT CONCENTRATION STARTER ON THE QUALITY OF KEFIR GOAT MILK - Permata Ika Hidayati, Aju Tjatur Nugroho Krisnaningsih, Cristhine Marisa Loniwila (Jurnal Sains Peternakan, 2017)
ABSTRACT The aim of this study was to investigate the effect of using different starter concentration on the quality of goat milk kefir. The material used in this study is the starter of goat's milk and kefir granules. This research method used was experimental studies designed using completely randomized design (CRD), which consists of 4 treatment that P0: goat's milk without starter, P1: goat milk were given starter kefir 3% fermented, P2: goat milk were given starter kefir 3 , 5% fermented, P3: goat milk kefir starter by 4% fermented. Each treatment was repeated 3 times, the measured variables, namely pH, protein content, and organoleptic tests. Data were analyzed using analysis of variance, if there are differences continued using Duncan test, while the organoleptic test were analyzed using Kruskal Wallis. Based on the results of the study indicate that the use of starter concentration provides highly significant effect (P <0.01) on pH and protein content of goat milk kefir. The highest pH at concentrations of 0% then successively concentrations of 3%, 3.5%, 4% at 6.5, 4.4, 3.5, 3.4. The highest protein content at a concentration of 4% and then successively 3.5%, 3%, 0% of 3.8%, 3.7%, 3.4%, 2.4%, while the organoleptic tests there are real effect (P> 0.05). The conclusion from this study is the use of starter concentration producing quality goat milk kefir quality is best at a concentration of 4%. It is advisable to use goat milk kefir with a concentration of 3%, 3.5% as suitable for consumption and meets the standards of fermented milk. Keywords: Kefir goat milk, pH, protein content, organoleptic test